1992
DOI: 10.1093/ajcn/56.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olestra, a noncaloric fat substitute, on daily energy and fat intakes in lean men

Abstract: Nutrient and energy intakes, hunger, and fullness were examined after the replacement of 36, 20, or 0 g fat in breakfast with olestra, a noncaloric fat substitute. Twenty-four lean, nondieting men (aged 21-30 y) participated in a placebo-controlled, three-condition crossover design. Self-selected, ad libitum intakes at lunch and dinner were monitored in the laboratory. Evening snacks and breakfast the next day were assessed through food diaries. Visual-analog-scale ratings including hunger and fullness were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…In a previous study sucrose polyester (SPE) was substituted for fat at a breakfast meal and subjects were free to compensate for the reduction in energy over the remainder of the day. Indeed, subjects demonstrated good Compensation for the larger 34 g fat replacement Rolls et al 1992) at least to the high dose of SPE. Conversely in two recent studies fat intake was reduced by 55 g using SPE substitution over 1 d by making small SPE substitutions on either four (meal) or five (snack) eating occasions.…”
Section: (Received 22 December 1994 -Revised 24 July 1995 -Accepted 8mentioning
confidence: 96%
See 1 more Smart Citation
“…In a previous study sucrose polyester (SPE) was substituted for fat at a breakfast meal and subjects were free to compensate for the reduction in energy over the remainder of the day. Indeed, subjects demonstrated good Compensation for the larger 34 g fat replacement Rolls et al 1992) at least to the high dose of SPE. Conversely in two recent studies fat intake was reduced by 55 g using SPE substitution over 1 d by making small SPE substitutions on either four (meal) or five (snack) eating occasions.…”
Section: (Received 22 December 1994 -Revised 24 July 1995 -Accepted 8mentioning
confidence: 96%
“…The different experimental outcomes may be attributed to the distinct methodologies which have been employed. Certain studies have found that fat has an equivalent satiating efficiency to carbohydrate and that manipulations of energy using fat are accurately compensated for by later adjustments in intake (Foltin et al 1990;Rolls et al 1992). Other studies have demonstrated that addition of a fat supplement to a basic breakfast has no effect on subsequent intake whilst an isoenergetic carbohydrate supplement exerts a short-term effect on appetite control (Cotton et al 1994).…”
Section: (Received 22 December 1994 -Revised 24 July 1995 -Accepted 8mentioning
confidence: 99%
“…The ®nding that our subjects did not end up preferring the more energy-dense ice cream suggests that individuals following a weight loss regimen will not necessarily be inclined to switch to normocaloric versions when freely available. Our data do not allow us to predict how consumers might respond when the reduced fat and energy content of their foods are unconcealed, although some recent reports (Rolls et al, 1992;Miller et al, 1995) suggest that subjects tend to eat more of a food when they know that the fat content has been reduced.…”
Section: Discussionmentioning
confidence: 64%
“…Most humans live in closed economies; within that context some encounters with food are essentially an open economy, such as the time available for lunch or its net cost. Many studies in humans have examined within-meal regulation, such as the effect of a preload or first course on intake of a test meal or second course [25]. However, these types of study often show carry-over effects whenever multiple meals (approaching a closed economy) have been included in the analysis [25,26].…”
Section: Open and Closed Economiesmentioning
confidence: 99%